Rapid Assessment of an African District Health System : Test of a Planning Tool - Nordberg, Erik; Oganga, Hezron; Kazibwe, Sam; Onyango, Jared (The International Journal of Health Planning and Management, 1993)
Occasional rapid health care system assessments are potentially useful for planning, for monitoring health care systems development over time, and for comparing health systems in different areas. With the decentralization of health sector management, for example in Kenya, there is a growing need of such assessments at district and sub-district levels. Can rapid assessments be conducted at affordable cost at these levels? What variables and methods are feasible? This paper reports on a rapid health system assessment conducted in rural Kenya during 1991. It required the completion at each health facility of a self-administered questionnaire which included questions on resources, health care programmes, management, service output, and prominent problems. It also included interviews with officers in charge of each health institution in the sub-district and an examination of records and reports available at each facility The paper presents the range of issues addressed, the indicators used, the methods applied, the problems encountered, the costs of the assessment, and a small selection of the findings. We conclude that the assessment model is manageable at district level with modest planning and analysis support from central level. Field staff need more precise instructions for completion of the questionnaire, and more population-based estimates need to be calculated. Reassessment taking place every 3–5 years should be adequate for monitoring the process of change in the local health care system.